Prevalence of dementia in an elderly rural population: effects of age, sex, and education. Issue 6 (June 1996) - Prencipe, M; Casini, A R; Ferretti, C; Lattanzio, M T; Fiorelli, M; Culasso, F
Abstract : OBJECTIVES--To estimate the prevalence of dementia in an elderly rural population and to determine the effects of age, sex, and education. METHODS--To obtain prevalence estimates of both cognitive impairment and dementia a door to door two phase population survey was carried out in three rural villages in central Italy. Of 1147 inhabitants older than 64, 968 (84.4%) completed the protocol. RESULTS--The prevalence rates (cases per 100 population over 64) were 8.0 for dementia and 27.3 for cognitive impairment. The prevalence rate for dementia did not differ between men and women (7.9 v 8.2), but increased with age (from 1.1 at age 65-69 to 34.8 at age 90-96). Subjects with less than three years of schooling had a significantly higher prevalence of dementia (14.6; 95% confidence interval (95% CI) 10.2-19.1) than subjects with three or more years of schooling (5.9; 95% CI 4.2-7.7). At the multivariate logistic analysis, the risk related with a low level of education was still present after adjustment for age and sex (OR = 2.0; 95% CI 1.2-3.3). Alzheimer's disease was diagnosed in 64% of the 78 demented patients, vascular dementia in 27%, and other dementing diseases in 9%. CONCLUSIONS--In both Alzheimer and vascular dementia subtypes, the prevalence rates did not differ between men and women, but increased with age and were higher in subjects with a low level of education.